2014
DOI: 10.1080/01496395.2014.965260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Red Marine AlgaKappaphycus alvareziias Biosorbent for Methylene Blue: Isotherm, Kinetic, and Mechanism Studies

Abstract: In this work, non-living red seaweed (Kappaphycus alvarezii) biomass was investigated as a new biosorbent of methylene blue from aqueous solution. The effect of operational parameters such as equilibrium pH, agitation time, initial dye concentrations and biosorbent dosage on the biosorption capacity of Kappaphycus alvarezii was studied. The equilibrium solution pH was found to profoundly affected methylene blue sorption capacity of Kappaphycus alvarezii with pH 8 found to be optimum. Evidence from Fourier-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…One particular pollutant, water-soluble organic compounds, has proven difficult to remove from water by traditional methods (Huang, 2010;Singh, 2004;Aboulhassan, 2006;Salmiati, 2007;Vijayaraghavan, 2015). Recently, the advanced oxidation processes (AOPs), based on the in-situ generation of hydroxyl radicals (·OH), have been investigated extensively for the removal of aqueous organics (Nishiyama, 2015;Zeng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One particular pollutant, water-soluble organic compounds, has proven difficult to remove from water by traditional methods (Huang, 2010;Singh, 2004;Aboulhassan, 2006;Salmiati, 2007;Vijayaraghavan, 2015). Recently, the advanced oxidation processes (AOPs), based on the in-situ generation of hydroxyl radicals (·OH), have been investigated extensively for the removal of aqueous organics (Nishiyama, 2015;Zeng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass from marine macroalgae and seagrasses can be obtained in large quantities at a low price, provided that their harvesting is sustainable and does not affect the ecosystem balance in coastal areas. Different species of marine algae have been used to remove various metal ions, colorants (dyes) and other pollutants from water (Sheng et al, 2007;Bhatnagar et al, 2012;Aytas et al, 2014;Navarro et al, 2014;Rathod et al, 2014;Vijayaraghavan et al, 2015;Jerold and Sivasubramanian, 2016;Ungureanu et al, 2016;Mokhtar et al, 2017;Vigneshpriya et al, 2017;Arumugam et al, 2018;Kishore Kumar et al, 2018;Silva et al, 2019;Bouzikri et al, 2020; Coração et al, 2020;Fabre et al, 2020;Safarik et al, 2020a,b;Shobier et al, 2020; Table 1). Also, waste macroalgae biomass obtained after selected industrial processes can be employed for the same purposes (Safarik et al, 2018;Santos et al, 2018).…”
Section: Biosorbentsmentioning
confidence: 99%
“…Water hyacinth compost was utilized to study biosorption; efficient microorganisms were used to create this compost and to use biosorption to get rid of basic dyes [47]. An evaluation of the red marine alga AlgaKappaphycus alvareziias as a biosorbent for MB biosorption was reported in [48]. A study of the biosorption of MB onto Gracilaria corticata, a red seaweed, can be found in [49].…”
Section: Introductionmentioning
confidence: 99%